Creating Value In An Introductory Business IS And IT Unit - Aitken, Ashley; Hatt, Gillian (Deakin University; Geelong; Victoria; Australia, 2012)
Given the downturn in student enrolments in Information Systems (IS) and Information Technology (IT) units, and the poor performance of a first-year IS and IT common-core unit in a business school, a new unit was developed. Action and design science research methods were employed. The new unit has a unique focus on two key skills and on modern IT and information literacy. The first skill involves describing information systems, and the second, determining how to create business value with IT in specific business contexts. Modern IT tools like a Web-based productivity suite and professional networking services are introduced, together with advanced search techniques and services and an information quality evaluation framework. The evaluation of the utility and efficacy of the unit is based on the institutional standard student feedback survey and unsolicited feedback. The unit has achieved a significant improvement in evaluation results and feedback from students, as well as converting students who were previously averse to IS and IT to study further in these areas.